Lithium–Iron Fluoride Battery with In Situ Surface Protection. (5th February 2016) - Gu, Wentian; Borodin, Oleg; Zdyrko, Bogdan; Lin, Huan‐Ting; Kim, Hyea; Nitta, Naoki; Huang, Jiaxin; Magasinski, Alexandre; Milicev, Zoran; Berdichevsky, Gene; Yushin, Gleb
Abstract : Lithium–metal fluoride (MF) batteries offer the highest theoretical energy density, exceeding that of the sulfur–lithium cells. However, conversion‐type MF cathodes suffer from high resistance, small capacity utilization at room temperature, irreversible structural changes, and rapid capacity fading with cycling. In this study, the successful application of the approach to overcome such limitations and dramatically enhance electrochemical performance of Li–MF cells is reported. By using iron fluoride (FeF2 ) as an example, Li–MF cells capable of achieving near‐theoretical capacity utilization are shown when MF is infiltrated into the carbon mesopores. Most importantly, the ability of electrolytes based on the lithium bis(fluorosulfonyl)imide (LiFSI) salt is presented to successfully prevent the cathode dissolution and leaching via in situ formation of a Li ion permeable protective surface layer. This layer forms as a result of electrolyte reduction/oxidation reactions during the first cycle of the conversion reaction, thus minimizing the capacity losses during cycling. Postmortem analysis shows the absence of Li dendrites, which is important for safer use of Li metal anodes. As a result, Li–FeF2 cells demonstrate over 1000 stable cycles. Quantum chemistry calculations and postmortem analysis provide insights into the mechanisms of the passivation layer formation and the performance boost. Abstract : In situ formation of an effective protective surface layer on iron fluoride (FeF2 )‐based composite cathodes prevents the cathode dissolution and allows for 1000 stable cycles in high energy density Li–FeF2 cells. Quantum chemistry calculations and postmortem analyses provide insights into the mechanisms of the protective layer formation and the performance boost.